Fostering green creativity through environmental values: The role of intrinsic motivation, environmental identity and green HR practices - Ali Ansari; Shahid Mahmood; Kanwal Iqbal Khan; Farwa Asghar (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
Employee green creativity is the main instrument to enhance employees' and organizational performance. Environmental values are considered a healthier predictor of employees' green creativity. But some supporting mechanisms are also required that may influence green creativity through ecological values. This study explores the relationship among environmental values and employees' green creativity based on the value belief norm and supply value fit theories. Moreover, the intervening mechanism of intrinsic motivation, ecological identity, and the moderating role of green HR practices is also investigated. A survey was conducted among employees working in the hospitality industry to examine the relationship between environmental values, green creativity, intrinsic motivation, environmental identity, and green HR practices. Process macros results reveal that when management focuses on ecological importance, the inherent motivation and environmental identity act as an intermediary mechanism that indirectly influences green creativity in line with Green HR Practice.
Keywords: 330; Environmental values; green creativity; intrinsic motivation; environmentalidentity; green HR practices; hotel industry